Transcriptome analysis of mud crab (Scylla paramamosain) gills in response to Mud crab reovirus (MCRV). Issue 60 (January 2017) - Liu, Shanshan; Chen, Guanxing; Xu, Haidong; Zou, Weibin; Yan, Wenrui; Wang, Qianqian; Deng, Hengwei; Zhang, Heqian; Yu, Guojiao; He, Jianguo; Weng, Shaoping
Abstract: Mud crab ( Scylla paramamosain ) is an economically important marine cultured species in China's coastal area. Mud crab reovirus (MCRV) is the most important pathogen of mud crab, resulting in large economic losses in crab farming. In this paper, next-generation sequencing technology and bioinformatics analysis are used to study transcriptome differences between MCRV-infected mud crab and normal control. A total of 104.3 million clean reads were obtained, including 52.7 million and 51.6 million clean reads from MCRV-infected (CA) and controlled (HA) mud crabs respectively. 81, 901, 70, 059 and 67, 279 unigenes were gained respectively from HA reads, CA reads and HA&CA reads. A total of 32, 547 unigenes from HA&CA reads called All-Unigenes were matched to at least one database among Nr, Nt, Swiss-prot, COG, GO and KEGG databases. Among these, 13, 039, 20, 260 and 11, 866 unigenes belonged to the 3, 258 and 25 categories of GO, KEGG pathway, and COG databases, respectively. Solexa/Illumina's DGE platform was also used, and about 13, 856 differentially expressed genes (DEGs), including 4444 significantly upregulated and 9412 downregulated DEGs were detected in diseased crabs compared with the control. KEGG pathway analysis revealed that DEGs were obviously enriched in the pathways related to different diseases or infections. This transcriptome analysis provided valuable information on gene functions associated with the response to MCRV in mud crab, as well as detail information for identifying novel genes in the absence of the mud crab genome database. Highlights: First transcriptome of Mud crab gills response to Mud crab reovirus infection using Illumina Hiseq 2000. A total of 104.3 million clean reads were obtained, and 81, 901, 70, 059 and 67, 279 unigenes were gained respectively from HA reads, CA reads and HA&CA reads. About 13, 856 DEGs were detected in diseased crabs compared with the control, including 4444 significantly upregulated and 9412 downregulated DEGs. Ten of differently expressed genes were selected for validation with RT-qPCR. Immune-related genes involved in Wnt signaling pathway, MAPK signaling pathway and apoptosis pathway were focused.